Online Business Simulations : Good Practice Guide. - Benckendorff, Pierre; Lohmann, Gui; Pratt, Marlene; Reynolds, Paul; Strickland, Paul; Whitelaw, Paul (Office for Learning and Teaching, 2015)
This project evaluated and promoted pedagogies that enhance the learning outcomes of online simulations in business and related fields. Business simulations offer authentic learning experiences that mirror real world problems and enable students to practise and develop graduate capabilities, technical skills and strategic decision making skills. Emerging technologies along with increased bandwidth are creating new opportunities for online and cloud-based simulations and provide improved flexibility and portability for students. Simulations also hold some promise of complementing other innovations in online education, including MOOCs. However, online simulations are not effective unless they are embedded within a pedagogic framework that optimises learning outcomes. Project outcomes included workshops and an online toolkit of good practice guides, case studies, video vignettes, assessment and evaluation tools for institutional leaders and business educators.